2014
DOI: 10.4103/2249-4863.130267
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and psychiatric morbidity: a profile from a tertiary care centre of Eastern India

Abstract: Context:Psoriasis has an impact on psychology of the patients. There is a dearth of studies regarding this field in eastern India.Aims and Objectives:The primary objective of this study is to evaluate the psychiatric morbidity in psoriasis and secondary objective is to assess the morbidity in all eight dimensions of psychosocial and physical aspects, i.e. cognitive, social, discomfort, limitations, depression, fear, embarrassment and anger.Settings and Design:Institutional based case control study.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…[ 3 41 ] The effect of psychiatric morbidity on severity of psoriasis has also been studied individually. [ 4 5 6 7 ] None of the studies reviewed here have compared the quality of life and PASI scores in patients with and without psychiatric morbidity. We have tried to investigate the effect of depression/anxiety on quality of life and severity of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 41 ] The effect of psychiatric morbidity on severity of psoriasis has also been studied individually. [ 4 5 6 7 ] None of the studies reviewed here have compared the quality of life and PASI scores in patients with and without psychiatric morbidity. We have tried to investigate the effect of depression/anxiety on quality of life and severity of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Many studies done worldwide have shown that psychiatric comorbidities are frequently found among patients with psoriasis. [ 4 5 6 7 8 ] In view of the paucity of Indian research pertaining to the psychological aspects of psoriasis; it is necessary for further research to be conducted specifically in our cultural milieu.…”
Section: Introductionmentioning
confidence: 99%
“…5 Psoriasis is a chronic inflammatory disorder that has a major impact on socioeconomic aspects of a patient's life. 26 It can produce psychological stress, embarrassment, disgrace, and physical discomfort. 27 Patients with psoriasis have a high risk of depression, anxiety, and may develop suicidal tendencies.…”
Section: Psoriasis: "The Traumatizing Aspects"mentioning
confidence: 99%
“…The skin diseases can result in considerable psychological distress, an important clinical feature of many cutaneous diseases . Psoriasis is a chronic inflammatory disorder that has a major impact on socioeconomic aspects of a patient's life . It can produce psychological stress, embarrassment, disgrace, and physical discomfort .…”
Section: Introduction To Psoriasismentioning
confidence: 99%
“…It affects 1.4%–2.0% of the population and comprises 2.6% of skin-related visits to primary care physicians or between 0.3% and 0.6% of all visits to family physicians. [1] In India, the prevalence of psoriasis varies from 0.44% to 2.8%, it is twice more common in males compared to females, and most of the patients are in their third or fourth decade at the time of presentation. [2]…”
Section: Introductionmentioning
confidence: 99%